The Evaluation of Aortic Diameter Changes During Long-Term Follow-Up After Endovascular Treatment of Acute Blunt Traumatic Thoracic Aortic Injuries. (July 2018) - Fontana, Federico; Macchi, Edoardo; Piacentino, Filippo; Cardim, Larissa Nocchi; Marchi, Giuseppe De; Barbosa, Fabiane; Piffaretti, Gabriele; Novario, Raffaele; Rampoldi, Antonio Gaetano; Fugazzola, Carlo
Purpose: To evaluate the variations in aortic diameters and long-term results in patients who underwent thoracic endovascular aortic repair (TEVAR) for acute blunt traumatic thoracic aortic injuries (BTTAIs). Materials and Methods: We retrospectively evaluated 23 patients with a mean age of 39 years (range: 17-74 years) who underwent TEVAR for BTTAI between October 2000 and November 2014. All of the patients underwent computed tomography angiography (CTA) before hospital discharge as a baseline imaging for the subsequent follow-up examinations. The technical success, overall survival, and complications were evaluated. Furthermore, the aortic diameters outside of the stent-graft (1 cm proximal and 1 cm distal to the stent-graft) and the aortic diameters within the stent-graft (2 cm distal to the proximal end and 2 cm proximal to the distal end) were assessed. The diameters at baseline on CTA were compared with those of the latest available follow-up examination. Results: Technical success was 100% with a mean follow-up of 65.4 months (range: 12-171 months). No death was registered, and 2 (8.7%) of 23 endograft-related complications (1 stent-graft distal infolding and 1 endoleak 2 and 4 months after the procedure, respectively) were observed. An increase in aortic diameter either proximal or distal to the stent-graft (mean value 0.7 and 0.5 mm, respectively) or within the stent-graft (mean value of 0.5 mm for both proximal and distal diameters) was registered (mean follow-up at 65.4 months, range: 12-171 months). Conclusion: Aortic dilatation following TEVAR for BTTAI is minimal during long-term follow-up. Endovascular treatment represents a durable and safe option in acute BTTAIs.